PARTIAL MELTING EXPERIMENTS ON PERIDOTITE AND ORIGIN OF MID-OCEAN RIDGE BASALT - Kushiro I. (My University, 2001)
Recent partial melting experiments on peridotite indicate that mantle peridotites with Mg# 89 can produce primitive mid-ocean ridge basalt by partial melting at pressures greater than 1.5 GPa followed by extensive olivine fractionation. Polybaric incremental batch melting or stepwise fractional melting experiments indicate that the compositions of accumulated incremental melts formed along a mantle adiabat in the pressure range 2.0-1.0 and 2.0-0.5 GPa are close to, but slightly more olivine-rich than, those of primitive mid-ocean ridge basalt, and that the amount of accumulated incremental melts is significantly smaller than that of batch partial melts formed for the same potential temperature. The melting in adiabatically ascending mantle beneath mid-ocean ridges would cease at depths >15 km because of the inflection of the solidus of mantle peridotite.